Oxidant/antioxidant status, paraoxonase activity, and lipid profile in plasma of ovariectomized rats under the influence of estrogen, estrogen combined with progesterone, and genistein - Agacayak E; Basaranoglu S; Tunc SY; Icen MS; Findik FM; Kaplan I; Evliyaoglu O; Gul T (Drug Design, Development and Therapy, 2015)
Elif Agacayak,1 Serdar Basaranoglu,2 Senem Yaman Tunc,1 Mehmet Sait Icen,1 Fatih Mehmet Findik,1 Ibrahim Kaplan,3 Osman Evliyaoglu,3 Talip Gul1 1Department of Obstetrics and Gynecology, Dicle University School of Medicine, Diyarbakir, Turkey; 2Department of Obstetrics and Gynecology, Idil State Hospital, Sirnak, Turkey; 3Department of Biochemistry, Dicle University School of Medicine, Diyarbakir, Turkey Introduction: The aim of this study was to investigate whether estradiol (E2), E2 combined with progesterone (Prog) (E2/Prog), and genistein (Gen) treatment had antioxidative and antihyperlipidemic effects in the plasma of ovariectomized (OVX) rats.Materials and methods: Adult female Sprague–Dawley rats were divided into five groups. Rats in all groups, except for those in a sham group, underwent bilateral ovariectomy under general anesthesia. The groups were as follows: sham group; control OVX group; group treated with estrogen (0.014 mg/kg 17-β E2); group treated with a combination of E2 and Prog (0.014 mg/kg 17-β E2 plus 0.028 mg/kg drospirenone), and group treated with Gen (10 mg/kg/day). Plasma of rats of each treatment group was analyzed to determine the total antioxidant status, total oxidant status, paraoxonase activity, lipid profile, high-density lipoprotein (HDL-chol), low-density lipoprotein (LDL-chol), total cholesterol (Total-C), triacylglycerols, lipoprotein (a), and oxidative stress index.Results: Plasma Total-C levels and body weight increased in all the OVX groups compared with the sham group (P<0.005). The group treated with E2 had significantly elevated total oxidant status, oxidative stress index, LDL-chol, and Total-C compared with the control group (P<0.005). Gen treatment might lead to lower LDL-chol and Total-C levels compared with E2 treatment.Conclusions: Gen treatment might be preferred to E2 treatment for treatment of menopausal symptoms in patients at risk for cardiovascular diseases. However, considering the small sample size of this study, larger studies are needed in this area. Keywords: genistein, menopause, cardiovascular diseases